Ordination of the clergy and ecclesiastical law - Krafl, Pavel (Bogoslovni vestnik, 2024)
The subject of the study is the issue of ordination law in the Prague, Olomouc, and Litomyšl dioceses in the Middle Ages. The legal rules that were published in provincial and diocesan synods and which regulated the form of ordination are presented. The oldest preserved order of ordination of the clergy is from the time of Bishop of Olomouc Henricus Zdík (1126–1150). Instructions for the ordination of the clergy are included, for example, in the pontifical of Bishop of Litomyšl Albert of Šternberk. Ordinations were recorded in ordination books, the Prague ordination books from the years 1395–1416 being a particularly valuable source. The Hussite revolution brought significant encroachment on the functioning of the church in the Prague archdiocese and in the Litomyšl diocese. The bishopric of Litomyšl was completely dissolved, while the Prague archbishopric was not occupied by an ordinary, which caused complications in the ordination of priests.
Keywords: Bohemia; Bohemija; cerkveno pravo; ecclesiastical law; middle ages; ordinacija duhovnikov; ordinacijsko pravo; ordination law; ordination of the clergy; Prague Ecclesiastical Province; praška cerkvena provinca; srednji vek